Three-dimensional Magnetotelluric Inversion and Magnetic for The Characterization of The Geothermal Field Reservoir Zone “X” - Ridho Hanan Asrowi; Yunus Daud; Abdul Latif Ashadi; Syouma Hikmahtiar; Ahmad Said (CV FOUNDAE, 2023)
Geothermal as an alternative energy source that is renewable and environmentally friendly has an important role in providing domestic energy needs. Exploration is one of the most important stages in the development of geothermal energy because it can minimize the risk at the stage of exploitation and development. Geophysical methods such as geomagnet and magnetotelluric are one of the methods used in exploration. Magnetic method can provide information on the description of rock demagnetization due to the presence of heat source. However, the magnetotelluric method will provide information about rock type resistance on geothermal fields. The existence of heat source using the geomagnetic method is represented by a low anomaly value as an indication of demagnetized rocks. The results of 3D inversion processing show a low value of type resistance in the area and form an updome. The correlation of the two results of processing the data can be seen in the southern part of the